2002
DOI: 10.4049/jimmunol.168.3.1139
|View full text |Cite
|
Sign up to set email alerts
|

Synergy Between CD40 Ligation and IL-4 on Fibroblast Proliferation Involves IL-4 Receptor Signaling

Abstract: Fibrosis can be an undesired consequence of activated cellular immune responses. The purpose of this work was to determine whether CD40 ligation and the pro-fibrotic cytokine IL-4 interact in regulating fibroblast proliferation and collagen production, and, if so, the mechanisms used. This study found that the combination of IL-4 and ligation of CD40 on the fibroblast cell surface had synergistic effects in stimulating fibroblast proliferation. In contrast, CD40 ligation negated the inhibitory effects of IFN-γ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 57 publications
5
44
0
Order By: Relevance
“…Thus, these data from the C57BL/6 mice are consistent with a minimal, if any, direct role for IL-4 in the fibrotic response, as previously suggested (9). The basis for this lack of IL-4 responsiveness in C57BL/B6 fibroblasts remains to be determined, but may be due to possible absence of adequate and functional receptor(s) and/or synergistic activation by molecules such as CD40 ligand (51)(52)(53)(54). In addition, the fact that transgenic mice overexpressing IL-4 fail to develop significant fibrosis (6,12) may reflect an intrinsic difference in the responsiveness of murine fibroblasts to IL-4 relative to the mouse background strain used (C57BL/6).…”
Section: Discussionsupporting
confidence: 67%
“…Thus, these data from the C57BL/6 mice are consistent with a minimal, if any, direct role for IL-4 in the fibrotic response, as previously suggested (9). The basis for this lack of IL-4 responsiveness in C57BL/B6 fibroblasts remains to be determined, but may be due to possible absence of adequate and functional receptor(s) and/or synergistic activation by molecules such as CD40 ligand (51)(52)(53)(54). In addition, the fact that transgenic mice overexpressing IL-4 fail to develop significant fibrosis (6,12) may reflect an intrinsic difference in the responsiveness of murine fibroblasts to IL-4 relative to the mouse background strain used (C57BL/6).…”
Section: Discussionsupporting
confidence: 67%
“…18 In vitro studies have further confirmed the stimulatory effects of IL-4 and suppressive effects of IFN-␥ on fibroblast proliferation and collagen deposition. 19,20 It is therefore likely that Th2 cytokines are important for the development of fibrosis in the pericardium in EAM. Predominant Th2 responses in the absence of IFN-␥ in EAM are also demonstrated by increased numbers of eosinophils in the pericardium.…”
Section: Discussionmentioning
confidence: 99%
“…Predominant Th2 responses in the absence of IFN-␥ in EAM are also demonstrated by increased numbers of eosinophils in the pericardium. Eosinophils have been reported to participate in the development of fibrosis, 19,21 including the cardiac fibrosis associated with Loffler's endocarditis. 22 In summary, this work describes a novel model of constrictive pericarditis, associated with the typical morphological features of pericarditis and a classic constrictive physiology.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Mononuclear cells infiltration, adhesion molecules (CD -17) are also involved in the disease process. [4,[22][23][24][25] In addition, total body irradiation and ocular toxicity from bone marrow transplantation. [1,16,26,27] The composition of the normal human ocular surface flora had been identified, and the most prominent ocular flora includes Staphylococcus epidermidis, S. aureus, and Diphtheroids.…”
Section: Discussionmentioning
confidence: 99%